Some Coincidence Point Theorems in Modular Spaces: Beberapa Teorema Titik Coincidence pada Ruang Bermodular - Afifah Hayati (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2022)
In metric spaces, there are quasi-contraction mappings and Suzuki-contraction mapping, that are generalization of contraction mappings. In this article, we give coincidence point theorems of quasi-contraction mappings and Suzuki-contraction mappings in modular spaces, that are generalizations of fixed point theorem of quasi-contractraction mappings and Suzuki-contraction theorem in modular spaces.